Association of age with health-related quality of life in a cohort of patients with systemic lupus erythematosus: the Georgians Organized Against Lupus study. (19th July 2016) - Plantinga, Laura; Lim, S Sam; Bowling, C Barrett; Drenkard, Cristina
Abstract : Objective: To examine whether older age was associated with lower health-related quality of life (HRQOL) among patients with systemic lupus erythematosus (SLE) and whether differential disease-related damage and activity explained these associations. Methods: We used cross-sectional data on 684 patients with SLE aged ≥20 years from the Georgians Organized Against Lupus cohort to estimate the associations between age (categorised as 20–39, 40–59 and ≥60 years) and HRQOL (Short Form-12 norm-based domain and physical component summary (PCS) and mental component summary (MCS) scores), using multivariable linear regression. We then examined the effect of disease-related damage and activity on these associations. Results: The mean age of the cohort was 48.2±13.1 years (range, 20–88 years), with 28.0%, 52.9% and 19.1% of participants being aged 20–39, 40–59 and ≥60 years, respectively; 79.0% were African-American and 93.7% were female. The mean PCS score was 39.3 (41.8, 38.7 and 37.4 among those aged 20–39, 40–59 and ≥60 years, respectively), while the mean MCS score was 44.3 (44.2, 43.8 and 46.1, respectively). In general, lower physical but not mental HRQOL scores were associated with older age. With adjustment, older ages (40–59 and ≥60, respectively, vs 20–39) remained associated (β (95% CI)) with lower PCS (−2.53 (−4.58 to −0.67) and −3.57 (−6.19 to −0.96)) but not MCS (0.47 (−1.46 to 2.41) and 1.20 (−1.52 to 3.92)) scores. Associations of age with HRQOL domain and summary scores were not substantially changed by further adjustment for disease-related damage and/or activity. Conclusions: Nearly one in five participants in this large, predominantly African-American cohort of patients with SLE was at least 60 years old. The associations of older age with lower physical, but not mental, HRQOL were independent of accumulated SLE damage and current SLE activity. The results suggest that studies of important geriatric outcomes in the setting of SLE are needed to inform patient-centred clinical care of the ageing SLE population.